2006
DOI: 10.1097/00004728-200607000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Recurrent Hemoptysis With MDCT Angiography

Abstract: CT bronchial angiography may help in the prediction of recurrent bleeding in patients with massive hemoptysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Finally, to date, the prediction of recurrent hemoptysis has also been addressed by several other authors. 2426 Jeong et al have reported the CT findings to predict recurrent hemoptysis in 58 patients who underwent bronchial artery embolization due to massive hemoptysis. By multivariate analysis, the total number of dilated bronchial and nonbronchial systemic arteries was a significant CT variable associated with the recurrence of hemoptysis.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, to date, the prediction of recurrent hemoptysis has also been addressed by several other authors. 2426 Jeong et al have reported the CT findings to predict recurrent hemoptysis in 58 patients who underwent bronchial artery embolization due to massive hemoptysis. By multivariate analysis, the total number of dilated bronchial and nonbronchial systemic arteries was a significant CT variable associated with the recurrence of hemoptysis.…”
Section: Discussionmentioning
confidence: 99%